Chapter Influence of Glycaemic Control on Cognitive Function in Diabetic Children and Adolescents - Campoy, Cristina (InTechOpen, 2018)
According to the World Health Organisation (WHO), the number of people with diabetes has risen to 422 million in 2014. Poorly managed diabetes leads to chronic hyper and/or hypoglycaemia, which are associated with neurological complications in type 1 (T1DM) and type 2 (T2DM) diabetes mellitus. Therefore, the primary target of diabetic treatment is to achieve a good glycaemic control (GC). In this chapter, we reviewed studies published up to September 2017 about GC and cognitive development in diabetic children and adolescents, as well as the nutritional approaches used for the management of diabetes in childhood, focusing on low glycaemic index (GI) diets. According to different studies, low GI diets effectively improve GC, which may reduce the risk of diabetes-related complications, such as cognitive dysfunction; however, the evidence is not sufficiently robust and the results are inconclusive. Despite the fact that, low GI diets are consistent with healthy eating recommendations and should be encouraged in the prevention and nutritional management of diabetes. Further research is needed in diabetic children and adolescents at risk, especially well-designed long-term randomised controlled trials, with larger sample size, to determine the true value of low GI diets on long-term GC and diabetes prevention and management.